Guaranteed to fail : Fannie Mae, Freddie Mac, and the debacle of mortgage finance - Acharya, Viral V. (Princeton University Press, 2011)
The financial collapse of Fannie Mae and Freddie Mac in 2008 led to one of the most sweeping government interventions in private financial markets in history. The bailout has already cost American taxpayers close to 150 billion, and substantially more will be needed. The U.S. economy--and by extension, the global financial system--has a lot riding on Fannie and Freddie. They cannot fail, yet that is precisely what these mortgage giants are guaranteed to do. How can we limit the damage to our economy, and avoid making the same mistakes in the future? Guaranteed to Fail explains how poorly desig.